Comparing probabilities in urns: A study with primary school students - Hernández-Solís, Luis Armando (2021)
The study aimed to explore the strategies used by Costa Rican primary school students when comparing urn probabilities. The sample was intentional and consisted of 55 6th graders. Using an interpretive approach, we analyzed the children’s responses to a questionnaire of five probability comparison items taken from previous studies, including different levels of proportional reasoning. Results indicate that problems in the first levels of proportional reasoning were solved easily by students, while problems at higher levels increased in difficulty. One-variable strategies, which compare only the favorable or unfavorable cases in both urns, are predominant; although there are correspondence strategies, few students show complete proportional reasoning. Aside from slight variations, results are similar to previous studies, which suggests that this task is influenced more by the child’s level of maturity than the instruction received.